2014
DOI: 10.1212/wnl.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and medication in REM sleep behavior disorder

Abstract: This large study confirms the association between comorbid depression and antidepressant use in iRBD. In addition, there was an unexpected association of iRBD with ischemic heart disease that was not explained by cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 10 publications
5
71
0
1
Order By: Relevance
“…This association has been frequently reported in other studies [42][43][44][45] and may reflect a complex relationship. Antidepressants can trigger RBD, perhaps via a direct modulation of serotonergic innervation of spinal interneurons [46].…”
Section: Characteristics Of Rbd Positive Participantssupporting
confidence: 85%
“…This association has been frequently reported in other studies [42][43][44][45] and may reflect a complex relationship. Antidepressants can trigger RBD, perhaps via a direct modulation of serotonergic innervation of spinal interneurons [46].…”
Section: Characteristics Of Rbd Positive Participantssupporting
confidence: 85%
“…26 In another multicenter case-control study including 318 idiopathic RBD cases and 318 matched controls (181 sleep disorder controls and 137 healthy volunteers), RBD cases reported more cardiovascular disease (odds ratio [OR] 1.6; 95% CI 1.0-2.5) relative to the controls, and the association became stronger when 181 sleep disorder controls were removed (OR 2.4; 95% CI 1.3-4.6). 27 In the same study, a correlation between RBD and a higher odds of having selfreported cerebrovascular disease was also observed (OR 1.3; 95% CI 0.7-2.6), although the association was not significant, which could be due to small number of cerebrovascular disease cases (n 5 38) and misclassification due to self-report nature. 27 There are several biological mechanisms that may explain the observed association between RBD and stroke.…”
Section: Insomniamentioning
confidence: 83%
“…27 In the same study, a correlation between RBD and a higher odds of having selfreported cerebrovascular disease was also observed (OR 1.3; 95% CI 0.7-2.6), although the association was not significant, which could be due to small number of cerebrovascular disease cases (n 5 38) and misclassification due to self-report nature. 27 There are several biological mechanisms that may explain the observed association between RBD and stroke. The association could be due to a more profound change, resulting from the disturbed sleep.…”
Section: Insomniamentioning
confidence: 83%
See 1 more Smart Citation
“…Understanding these risk factors is important, because besides risk of neurodegeneration, RBD carries the risk of sleep disruption and injury. From recent epidemiological studies of potential risk factors for RBD,3, 4, 5, 6 several identified risk factors are related to neurodegenerative diseases (e.g., head injury and olfactory dysfunction) and cardiovascular diseases (e.g., hyperlipidemia and physical inactivity) 3, 4, 5, 64, 5, 6 though in some of the studies,4, 5 this association did not reach statistical significance.…”
Section: Introductionmentioning
confidence: 98%